A new perspective on hematological malignancies: m6A modification in immune microenvironment - Yang, Shiyu; Xu, Liping; Zhuang, Haihui; Li, Fenglin; Lu, Ying (Frontiers in Immunology, 2024)
Immunotherapy for hematological malignancies is a rapidly advancing field that has gained momentum in recent years, primarily encompassing chimeric antigen receptor T-cell (CAR-T) therapies, immune checkpoint inhibitors, and other modalities.However, its clinical efficacy remains limited, and drug resistance poses a significant challenge. Therefore, novel immunotherapeutic targets and agents need to be identified. Recently, N6-methyladenosine (m6A), the most prevalent RNA epitope modification, has emerged as a pivotal factor in various malignancies. Reportedly, m6A mutations influence the immunological microenvironment of hematological malignancies, leading to immune evasion and compromising the anti-tumor immune response in hematological malignancies. In this review, we comprehensively summarize the roles of the currently identified m6A modifications in various hematological malignancies, with a particular focus on their impact on the immune microenvironment. Additionally, we provide an overview of the research progress made in developing m6A-targeted drugs for hematological tumor therapy, to offer novel clinical insights.